Solid Organ Transplantation During the COVID-19 Pandemic - Zhang, Hedong; Dai, Helong; Xie, Xubiao (Frontiers in Immunology, 2020)
Since December 2019, the ongoing coronavirus disease 2019 (COVID-19) pandemic has significantly affected solid organ transplantation (SOT) worldwide and has become a threat to the lives of SOT recipients. Here, we have reviewed, condensed, and organized the available information on COVID-19 to provide recommendations to transplant healthcare workers. Our review of reported cases shows that the symptoms of SOT patients with COVID-19 are similar to those of the normal population, but their severity and outcomes are worse. Thus far, there is no evidence that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) directly causes permanent damage to kidney, liver, or heart allografts.